New antimicrobial therapies used against fungi present in subgingival sites-A brief review - Orlandi Sardi, Janaina Cassia [UNESP]; Almeida, Ana Marisa Fusco [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Although the main reservoir of Candida spp. is believed to be the buccal mucosa, these microorganisms can coaggregate with bacteria in subgingival biofilm and adhere to epithelial cells. The treatment of periodontal disease includes scaling and root planning (SR?) associated with proper oral hygiene. However, some patients may have negative responses to different therapeutic procedures, with a continuous loss of insertion, so the use of antimicrobials is needed as an adjuvant to SRP treatment. The use of a broad-spectrum antibiotic, such as tetracycline and metronidazole, as an aid in periodontal treatment has also been a factor for the development of superinfections by resistant bacteria and Candida species, even in patients with HIV. In the dental practice, the most commonly used antifungals are nystatin and fluconazole. However, the introduction of new drugs like the next generation of azoles is essential before the onset of emergent species in periodontal disease. Plants are good options for obtaining a wide variety of drugs. This alternative could benefit a large population that uses plants as a first treatment option. Plants have been used in medicine for a long time and are extensively used in folk medicine, because they represent an economic alternative, are easily accessible and are applicable to various diseases. Herein, we briefly review the literature pertaining the presence of Candida sp. in periodontal pockets, the conventional antifungal resistance and new therapies that include natural antifungal agents are reviewed. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Candida spp; Fungi; Antifungal; Periodontal disease; New antimicrobial therapies